Crime in The American Society: Causes, Types and Government Solutions - DAHNOUN, Ahlam (University of Eloued جامعة الوادي, 2024)
This research discusses crime in the American society. It aims to find out the different causes and types of crime in the United States of America. Furthermore, it explores the government solutions to prevent and reduce crime rates. This research opts for documentary research design within a qualitative approach to collect and analyse the content of available documents. It also employs historical research to give a brief history of the evolution of crime in America. In addition, it explains the government strategies to prevent crime. The findings show that crime remains a significant challenge in America and there are different types of it like hate crimes, violence crimes, and property crimes. Also, the causes are various and complicated ranging from educational, to economic, sociological, and religious. However, there has been a noticeable decrease in crime rates recently due to the American government's efforts in the field of criminology ; including Law Enforcement Strategies such as Community Policing and Intelligence-Led Policing , Legislation and Criminal Justice Reform , Crime Prevention Programs, and Education and awareness . يناقش هدا البحث الجريمة في المجتمع الأمريكي. يهدف لإيجاد مختلف أنواع وأسباب الجريمة في الولايات المتحدة الأمريكية كذلك يكشف حلول الحكومة لمنع وتخفيض معدل الجرائم. تم استخدام اطار الأسلوب النوعي لجمع البيانات و تحليل الوثائق المتاحة . كذلك تم توظيف الأسلوب التاريخي لاعطاء تاريخ موجز لتطور الجريمة في الولايات المتحدة الأمريكية و لشرح استراتيجيات الحكومة المتخذة لمنع الجريمة. أظهرت النتائج ان الجريمة لازالت تشكل مشكلة كبيرة في أمريكا وأن هناك أنواع مختلفة للجريمة مثل جرائم الكراهية، جرائم العنف وجرائم الملكية، أيضا الأسباب متنوعة ومعقدة تراوحت بين تربوية واقتصادية إلى اجتماعية ودينية. لكن هناك تراجع ملحوظ في معدلات الجريمة مؤخرا و هذا راجع لجهود الحكومة الأمريكية في مجال علم الجريمة بما في ذلك استراتيجيات إنفاذ القانون مثل الشرطة المجتمعية والشرطة التي تقودها المخابرات ، التشريعات وإصلاح العدالة الجنائية ، برامج منع الجريمة ، التعليم والتوعية .
Literature and Civilization
Keywords: American society; causes; crime; solutions; types .; المجتمع الأمريكي ، الأسباب، الجريمة، الحلول، الأنواع